Market information ? rural kiosks and radio - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2008)
Market information points and a weekly radio programme are two strategies used by the Kenya Agricultural Commodity Exchange